NUMERICAL EXPLORATION OF CHEMICAL REACTION AND JOULE HEATING EFFECTS ON THE DYNAMICS OF THNF CU-TIO_2-SIO_2/H_2 O:HEAT AND MASS TRANSMISSION ANALYSIS - Lakshmi, Naga; Maheswari, Ch; Kanuri, Venkata Rao; Ramanaiah, J.V.; Durga Rao, R. S.; Bhagavan, V. S. (Journal of mechanics of continua and mathematical sciences, 2025)
This analysis attempts to explain the theoretical analysis of Joule heating and chemical reactions on the systematic flow of a ternary hybrid nanofluid. The flow of the tri-nanofluids was examined on thermal, momentum, and concentration boundary layers (BL). The physical problem was developed as a partial differential equation (PDEs). This was changed to total differential equations by suitable similarity variables. The Runge-Kutta, along with the shooting technique, was employed on the transformed flow equations. These solutions were presented in a pictorial form to discuss the physical problem, while the quantities of interest in engineering are tabulated. The Eckert number was found to enhance the thermal analysis by elevating the temperature along with the velocity distribution. The Joule heating along the magnetic field in the analysis was discovered to limit the speed of the fluid by reducing the velocity distribution.